Integrating buprenorphine treatment into office-based practice: a qualitative study. - Barry, Declan T; Irwin, Kevin S; Jones, Emlyn S; Becker, William C; Tetrault, Jeanette M; Sullivan, Lynn E; Hansen, Helena; O'Connor, Patrick G; Schottenfeld, Richard S; Fiellin, David A (Journal of general internal medicine, 2009)
Despite the availability and demonstrated effectiveness of office-based buprenorphine maintenance treatment (BMT), the systematic examination of physicians' attitudes towards this new medical practice has been largely neglected.
Keywords: Buprenorphine; Family Practice; Female; Humans; Interviews as Topic; Male; Office Visits; Opioid-Related Disorders; Primary Health Care; Qualitative Research